Plastic Use in Kathmandu’s Departmental Stores: Environmental Impacts and Alternatives - Thadathil, Boby Joseph; Pudasaini, Swarnika; Maharjan, Diya; Kafle, Richa (Journal of Multidisciplinary Research Advancements, 2025)
Plastic is widely used in retail shops and departmental stores in Kathmandu for packing, carrying, and storing goods due to its low cost and durability. However, its excessive use poses a significant environmental threat, causing pollution, harming human health, and damaging ecosystems. The research aims to investigate insights from owners and customers regarding their current plastic usage, the challenges they face in minimising plastic waste, and the potential for adopting eco-friendly alternatives. This study employed a quantitative method, using data collected from department stores across the Kathmandu Valley. A total of 320 respondents, including 160 store employees and 160 customers, were chosen through stratified random sampling. The data were collected through face-to-face interviews and 44 structured questionnaires to examine plastic use, awareness, and alternatives. The findings highlighted the need to reduce reliance on plastics and to identify implementation options for society. The shopkeepers in Kathmandu recommend eco-friendly shopping practices and aim to enhance public awareness about the environmental impacts of plastic usage. The study notes that effective implementation of sustainable solutions requires cooperation among the government, the commercial sector, and NGOs. The shopkeepers proposed that imposing strict penalties on plastic manufacturers and retailers that contravene regulations could significantly reduce plastic waste. Lastly, the findings revealed that consumers are more likely to adopt sustainable practices when offered affordable, convenient, eco-friendly options. This study demonstrates that reducing plastic use in department stores is not only necessary but also feasible when appropriate measures are implemented. If the government, businesses, and NGOs implement regulations, provide alternatives, and raise awareness, this can help reduce plastic waste and make Kathmandu a cleaner and more sustainable city.